2018
DOI: 10.1161/atvbaha.117.310491
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Semaphorin 7A Upregulation by Disturbed Flow Promotes Atherosclerosis Through Endothelial β1 Integrin

Abstract: Our findings indicate a significant role of Sema7A in atherosclerosis by mediating endothelial dysfunction in a β1 integrin-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 43 publications
2
74
0
Order By: Relevance
“…Subsequent work has shown that it enhances autoimmune encephalitis through Tcell-dependent cytokine production and that it can also increase the infiltration of neutrophils into sites of tissue hypoxia 19,20 . A role for Sema7a in the cardiovascular system has been described recently in atherogenesis 21 . Hu et al showed that disturbed flow resulted in an induction of Sema7a on vascular endothelium and that this results in an increased expression of leukocyte adhesion molecules on the endothelial surface.…”
mentioning
confidence: 93%
“…Subsequent work has shown that it enhances autoimmune encephalitis through Tcell-dependent cytokine production and that it can also increase the infiltration of neutrophils into sites of tissue hypoxia 19,20 . A role for Sema7a in the cardiovascular system has been described recently in atherogenesis 21 . Hu et al showed that disturbed flow resulted in an induction of Sema7a on vascular endothelium and that this results in an increased expression of leukocyte adhesion molecules on the endothelial surface.…”
mentioning
confidence: 93%
“…Synthetically considering the atheroprotection induced by Sema7A gene knockout in animal models 19 Considering potential limitations of this study, our results should be interpreted cautiously. The current study is a case-control study with a relatively small study population, and with the nature of the cross section for the association of Sema7A with AAS because measurements of Sema7A were only obtained after AAS onset.…”
Section: Ta B L E 1 Baseline Characteristics Of 105 Acute Atherothrommentioning
confidence: 89%
“…Sema3E also inhibits smooth muscle cell migration and proliferation, decreasing neointimal hyperplasia in animal model of atherosclerosis ( 23 ). Different from Sema3A and 3E, Sema7A favors atherosclerotic plaque development by increasing endothelial dysfunction in a β1 integrin-dependent manner ( 24 ). In fact, vessels under oscillatory disturbed shear stress show higher Sema7A levels, while Sema7A knockout (ko) mice have attenuated plaque formation ( 24 ).…”
Section: Atherosclerosis and Semaphorinsmentioning
confidence: 99%